RELIGIOUS INTELLECTUALISM AND SOCIETY: An Editorial Note - Raihani Raihani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
A dominant culture, which is usually rooted in religion, exists in every society (Buckingham, 2012). We can easily point to a number of countries to support this statement. The United States of America, England, and Australia are some of countries where the society is predominantly Christians. The cultures rooted in the Christian traditions can be seen and traced in people’s daily life, behaviors and interactions, even though, perhaps, many of the society members rejected any formal affiliation to Christianity. Even after secularization in which religious adherence was no longer valued, the influence of the long religious tradition remains intact in many of the world’s societies.